Barriers and facilitators to anal cancer screening among people living with HIV in Puerto Rico - Gabriela Cruz; Jeslie M. Ramos-Cartagena; José L. Torres-Russe; Vivian Colón-López; Karen J. Ortiz-Ortiz; Luis Pericchi; Ashish A. Deshmukh; Ana Patricia Ortiz (BMC, 2023)
Abstract Background Anal cancer (AC) disproportionally affects people living with HIV (PLWH). Although there are no consensus-based AC screening guidelines, experts recommend anal pap as a primary screening tool in settings where high-resolution anoscopy (HRA) is available. We aimed to assess barriers and facilitators to anal cancer screening in a sample of Hispanic PLWH in Puerto Rico. Methods To assess their knowledge and attitudes, we conducted a cross-sectional survey from 2020-2021 among PLWH in Puerto Rico (n = 212). Data was collected through a telephone interview that assessed information on sociodemographics, knowledge, and attitudes about AC, and the history of AC screening. The chi-square test, Fisher exact test, and logistic regression models were used to assess factors associated with screening uptake. Results Anal Pap and HRA awareness were 60.4% and 30.7%, respectively. Anal Pap and HRA uptake was 51.5% and 19.3%, respectively. The most common barriers for anal Pap and HRA were lack of knowledge about the test and lack of physician recommendation. MSM were more likely to have heard of anal Pap (OR: 2.15, 95% CI:1.30-3.54) than MSW. MSM (OR: 3.04, 95% CI: 1.79-5.19) and women (OR: 3.00, 95% CI: 1.72-5.20) were also more likely to have undergone anal Pap. Similarly, individuals with a history of genital warts were more likely to have heard of anal Pap and HRA and have undergone anal Pap and HRA. Awareness of where to go for concerns about anal health was positively associated with having received anal Pap and HRA. Conclusions With emerging evidence on the effectiveness of screening and treatment for anal cancer, several organizations are steering toward generating consensus-based anal cancer screening recommendations. Our study provides foundational data on barriers and facilitators to anal cancer screening in Puerto Rico that will be critical to informing screening implementation in this US territory.